Mugės ir jų vaidmuo prekybos struktūroje Vilniaus ir Kauno gubernijose 1861-1914 metais - Ambrulevičiūtė, Aelita (Lietuvos istorijos studijos, 2007)
Vilnius and Kaunas province didn't have large-scale fairs. Traditionally, they lasted 1-2 days, sometimes - a couple of weeks, rarely - a month. Each fair had its own traditions and specialization. Before the appearance of railway and factory production, fairs played a very important role in wholesale trade: the key transactions were carried out through the fairs system. Tendencies of fairs' decline appeared after the economic reforms in 1861.  With Lithuanian involvement in the interlocal market of trade, the importance of foreign and interregional trade was growing, and the network of domestic trade was increasing. However, the quantitative spread of the latter was decreasing the turnover of separate markets. Also, the expansion of the fairs network from the eighties of the 19th century noticeably decreased the trade turnovers of a separate fair and reduced the importance of fairs as a form of wholesale trade. Such a phenomenon should be explained not just by the economic backwardness of the country, domination of agrarian trade, but by the modernization of structures of transport, production, and commerce.  With the expansion of factory production and the increased extent of production after 1861, the seasonal prevalence of fairs and their locality were not meeting the modern requirements for the realization of goods. Permanent industry trade of consumer goods was creating modern outlet forms. Because of the specifics of trade in fairs, wholesale of factory goods didn't spread here even since the middle of the eighties when the number of factories and the amount of industrial goods were increasing. Just a small part of industrial goods for consumers' needs was getting into the fairs through the retail trade system, which was creating its own network for the realization of goods in the seventies-eighties of the 19th century. Since the end of the 19th century, the main goods assortment and the biggest part of trade turnover in Vilnius and Kaunas province fairs were the products of agriculture.  Laying of railways improved communication, constant trade relationships with the industrial centers began, which revitalized the interregional transportation of goods from/into abroad. With the permanent goods realization possibilities, the industrial enterprises did not have to wait for the coming fairs. Since then, industrial products were sold out through the modern permanent outlet system of goods (wholesale warehouses and special shops), and the products of agriculture in fairs and through special networks of wholesale warehouses, established for agricultural products. The latter took some part of fairs outlet and quantitatively decreased the transportation of goods into fairs. Such differentiation of the outlet for goods caused a great decrease in the trade turnover in fairs, their role in the trade structure fell down, and their importance was reduced just to the local level.  The decline of the latter was also influenced by the growth of the network of markets in the second part of the 19th century. Under the market conditions, the seasonal prevalence of fairs only partly satisfied peasants and artisans, since marts' working schedules were more constant (1-3 times a week), and they too were great competitors of the fairs. Wholesale warehouses, special consumer goods shops, and marts all decreased the importance of the fairs. Fairs became places for the realization of artisans' and farmers' production. There, artisans and farmers, making for the market, could sell their products without a mediator. That is why the increasing number of fairs was one effect of the growth of the commercialization of agriculture, integration of the peasant's economy into the market, and his conversion into an entrepreneur.